The CJEU Hyperlinks Trilogy: Is this the End of the Story? - Manteghi, Maryna (fi=Turun yliopisto|en=University of Turku|, 2016)
Generally, a hyperlink can be presented as an integral and the most important feature of the Internet, which interconnects websites with one another, thus simplifying the browsing around the Web. Nevertheless, the linking issue has become a key topic among legal scholars due to its inherent ability to infringe the exclusive rights of copyright owner of the linked content. Actually, the great concern is that a provision of hyperlinks may be amounted to an unauthorized act of communication the work to the public and hence, lead to the infringement of the exclusive rights of the copyright owner granted under Article 3 of the Directive 2001/29/EC. Therefore, the thesis analyzes the concept of “communication to the public” by examining its development, interpretation and application by the CJEU and the EU’s national courts in order to assess whether a hyperlink infringes copyright through violation of the “communication to the public” right. Accordingly, the thesis closely analysis the CJEU’s linking “trilogy”, the recent landmark cases: Svensson, BestWater and C More Entertainment, in order to understand the CJEU’s position in regards to copyright aspects of linking technique. Actually, the thesis argues that despite of the CJEU’s attempts to clarify the issue in its recent rulings, in reality, a long-awaited “peace” was partially achieved, as the decisions raise much more questions than one may presume. Thus the thesis suggests that those linking issues, which currently remain somewhat a “gray area”, would require further clarification from the CJEU.